Species Composition and Abundance of Zooplankton at Different Depths in the Waters of Teluk Makmur Subdistrict, Dumai City - Sinaga, Merisa Debora; Nurrachmi, Irvina; Samiaji, Joko (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Teluk Makmur in Dumai City is a coastal area experiencing ecological pressure due to human activities, such as tourism and industry. Changes in water quality in this region may affect the structure of the zooplankton community, which plays a crucial role in the food chain. This study aims to determine the species and abundance of zooplankton at various depths and stations. The research was conducted in November 2024 at Koneng Beach, Marina Beach, and Puak Beach. At each station, samples were collected at three depths (1 m, 3 m, and 5 m) using survey and purposive sampling techniques. Water quality parameters such as temperature, salinity, DO, pH, transparency, current, nitrate, and phosphate were also measured. Identification revealed five zooplankton species from the class Hexanauplia: Acartia sp., Calanus sp., Temora turbinata, Oithona sp., and Nauplius sp. The highest abundance was recorded at a depth of 5 m (41,542 ind/l), while the lowest abundance was found at depths of 1 m and 3 m (0 ind/l). Based on stations, the highest abundance was observed at Station I (27,694.67 ind/l) and the lowest at Station II (8,308.33 ind/l). One-way ANOVA test results showed no significant difference in zooplankton abundance either between depths or between stations (p > 0.05).